2020
DOI: 10.1016/j.molmet.2019.11.007
|View full text |Cite
|
Sign up to set email alerts
|

FDG uptake tracks the oxidative damage in diabetic skeletal muscle: An experimental study

Abstract: ObjectivesThe present study aims to verify the relationship between glucose consumption and uptake of 18F-2-deoxy-glucose (FDG) in the skeletal muscle (SM) of experimental models of streptozotocin-induced diabetes mellitus (STZ-DM).MethodsThe study included 36 Balb/c mice. Two weeks after intraperitoneal administration of saline (control group, n = 18) or 150 mg streptozotocin (STZ-DM group, n = 18), the two cohorts were submitted to an oral glucose tolerance test and were further subdivided into three groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
23
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 55 publications
5
23
0
1
Order By: Relevance
“…activity, induced by SOD1 G93A mutation, that would rather suggest a deceleration in glycolytic ux combined with a constant rate of cytosolic PPP. However, the divergent response of tracer retention and glycolytic ux to SOD1 G93A mutation closely agrees with a series of previous observations [10][11][12][13][14] documenting a relative independence between FDG uptake and glucose consumption. According to this evidence, tracer accumulation rate largely re ects the activation of H6PD catalytic function within the ER as also con rmed by the selective localization of the FDG uorescent analog, 2-NBDG, within the ER of transgenic muscles.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…activity, induced by SOD1 G93A mutation, that would rather suggest a deceleration in glycolytic ux combined with a constant rate of cytosolic PPP. However, the divergent response of tracer retention and glycolytic ux to SOD1 G93A mutation closely agrees with a series of previous observations [10][11][12][13][14] documenting a relative independence between FDG uptake and glucose consumption. According to this evidence, tracer accumulation rate largely re ects the activation of H6PD catalytic function within the ER as also con rmed by the selective localization of the FDG uorescent analog, 2-NBDG, within the ER of transgenic muscles.…”
Section: Discussionsupporting
confidence: 91%
“…Quadriceps muscle side was randomly selected. Ex vivo FDG uptake of quadriceps and hearts was evaluated using the Ligand-Tracer White ® instrument (Ridgeview, Uppsala, SE) according to our previously validated procedure [12,14,19]. Brie y, the device consists of a betaemission detector and a rotating platform harboring a standard Petri dish.…”
Section: Ex Vivo Extraction Fraction Of Fdg and Glucosementioning
confidence: 99%
See 2 more Smart Citations
“…Although FDG uptake is commonly considered an index of glucose consumption, several studies recently reported a direct and strict link between tracer retention and the response to redox stress involving a selective activation of pentose phosphate pathway (PPP) triggered by hexose-6Pdehydrogenase (H6PD) within the endoplasmic reticulum (ER) [10]. This correlation fits the capability of this enzyme to recognize a large number of hexoses (including FDG-6P) as substrates and was documented in cancer cells [10][11], neurons and astrocytes [12], cardiomyocytes [13] and, more importantly, in skeletal muscles [14].…”
Section: Introductionmentioning
confidence: 74%